2021
DOI: 10.1136/bmj.m4957
|View full text |Cite
|
Sign up to set email alerts
|

Association between county level cannabis dispensary counts and opioid related mortality rates in the United States: panel data study

Abstract: Objective To examine county level associations between the prevalence of medical and recreational cannabis stores (referred to as dispensaries) and opioid related mortality rates. Design Panel regression methods. Setting 812 counties in the United States in the 23 states that allowed legal forms of cannabis dispensaries to operate by the end of 2017. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Substitution frequency is higher for patients using medical cannabis to treat comorbidities (such as the triad of pain, anxiety, and depression) than for those with a single condition. This impact is now seen at a population level—in US states where medical and recreational cannabis are widely used, deaths from opioid overdose have fallen 28…”
Section: Arguments Formentioning
confidence: 99%
“…Substitution frequency is higher for patients using medical cannabis to treat comorbidities (such as the triad of pain, anxiety, and depression) than for those with a single condition. This impact is now seen at a population level—in US states where medical and recreational cannabis are widely used, deaths from opioid overdose have fallen 28…”
Section: Arguments Formentioning
confidence: 99%
“…In addition to CBMPs, the majority of participants reported that they were currently using at least one prescribed medication while many reported using multiple medications, including both weak and strong opioids. A growing body of academic research suggests that individuals are using cannabis as a substitute for prescription drugs, particularly, narcotics/opioids ( 38 , 39 ). This is especially true if patients suffer from pain, anxiety and depression ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reiman and coauthors' (2017) survey of medical cannabis patients found that, among respondents who used opioids, 97% reported that cannabis helped them decrease opioid use (see Mercurio et al, 2019 for similar qualitative findings, Lucas, 2019 for similar results in Canada, and Corroon et al, 2017 in Washington). In 812 counties in U.S. states with legal cannabis, higher incidence of cannabis dispensaries was correlated with fewer opioid-related deaths, 2014-2018 (Hsu & Kovacs, 2021).…”
Section: Public Health and Safety Improvementsmentioning
confidence: 98%